Performance Analysis and Low Power Design of Voltage Level-up Shifters - Srikanth, B.; Nayak, Rameswari; Singh, Sangeeta; Harini, V. (International Journal of Engineering and Technology, 2018)
Voltage level-up shifters are widely used in dual supply applications and it acts as an interface between main core and input-output units. Low power with efficient level-up shifter is designed by reducing the transistor count and the proposed level-up shifters are capable of converting from sub-threshold to above threshold level signal. The strength of pull-down networks and pull-up networks are enhanced by employing a couple of current mirror circuits. The simulation results of the proposed level shifter in 180nm technology yields a power dissipation of 95.79nw, propagation delay of 41.23ns for an input voltage of 0.4V and input frequency of 1MHz, low supply voltage VDDL=0.4V, high supply voltage VDDH=1.8V. Proposed 14T Level shifter in 90nm Technology demonstrates a power dissipation of 54.8nw, propagation delay of 28.8ns for an input voltage of 0.2V and input frequency of 1MHz, VDDL=0.2V, VDDH=1.2V.Â Â